ANALISIS CLUSTER COVID-19 DI SUMATERA BARAT DENGAN METODE NON-HIRARKI (K-MEANS) - Afridho Afnanda; Arnellis Arnellis (UNIVERSITAS NEGERI PADANG, 2021)
COVID-19 has spread and has become a pandemic in almost all of the world, including in Indonesia. In Indonesia, this virus was first announced on March 2, 2020, until March 14 to 27, 2020, a total of 77,261 cases were identified. In an effort to stop the spread of COVID-19, the Indonesian government has made several policies that are expected to suppress the spread of this virus. Cluster analysis is a technical class, used to classify objects or cases into relatively homogeneous (same) groups called clusters. The type of data used is secondary data on COVID-19 in districts/cities of West Sumatra Province obtained from the West Sumatra Provincial Health Office and the COVID-19 task force website, where the data obtained is cumulative data from March 2020 to July 14, 2021. Optimization the number of K clusters using the elbow method to produce K=3, the results of the K-means cluster analysis with the number of K=3 concluded that the distance of members in the cluster is low and the distance between clusters is large